The issues and challenges faced by Malay cuisine in the foreign market / Rahman Abdullah ... [et al.] - Abdullah, Rahman; Arifin, Aniza; Samsudin, Azlina; Bachok, Sabaianah; Zahari, Harnizam (Universiti Teknologi MARA, Perlis, 2021)
The traditional food of a culture in a society is continuously inherited from the old generation to the new generation. The traditional element is an in-depth understanding of the function of each material, techniques of preparation, and the practice in our daily cooking. This understanding in the form of preparation, meal preparation, tips, use of certain equipment, and raw materials are mysteries difficult to be unravelled. The Malay cultural heritage food is an integral asset among Malaysians in general and the Malay race in particular. Malay cuisine is one of the special and unique blended of many traditions from around the region. However, when Malay culture and cuisine are introduced to other countries, they faced certain hurdles and challenges. This study investigates the issues and challenges faced by Malay cuisine in the foreign market. The points in question are, 1) Why are Malay cuisine difficult to be exported to other countries 2) Why Malay cuisine is less popular than cuisines from other countries? 3) What are the factors that make foods from a country of origin can be successfully exported? These issues and challenges will be parsed and discussed based on the existing written collection. Recommendations will be made on the mechanisms that enable the success of Malay cuisine food to be commercialized abroad, as well as future research examining the success factors of traditional food exported abroad.